Inhibition of the MyD88 signaling pathway could upregulates Ghrelin expression to synergistically regulate hepatic Echinococcus multilocularis-infected progression - Zhu, Jiang; Zhou, Tanfang; Chen, Guangfeng; Wu, Yuhui; Chen, Xia; Song, Ya; Tuohetali, Ayinula; Gao, Huijing; Pang, Dongming; Wen, Hao; Aimulajiang, Kalibixiati (Frontiers in Immunology, 2024)
IntroductionAE and whether the inhibition of the MyD88 inflammatory pathway can enhance Ghrelin expression to collaboratively modulate AE progression remains unclear.MethodsIn this study, we evaluated Ghrelin serum levels and changes in TLR4/MyD88/NF-κB pathway proteins and inflammatory factors in AE patients and E. multilocularis mouse models at different stages of infection (-4, -8, and -12 weeks). Additionally, we administered the MyD88 inhibitor TJ-M2010-5 intraperitoneally to infected mice to evaluate alterations in inflammation and Ghrelin levels, as well as disease progression.ResultsA decrease in serum Ghrelin levels in AE patients, whereas both Ghrelin and GHSR, along with TLR4/MyD88/NF-κB pathway proteins and markers of M1/M2 macrophage polarization, exhibited increased expression in the inflammatory cell zones surrounding hepatic lesions. Similar findings were observed in E. multilocularis-infected mice. M1-type inflammatory expression predominated throughout the infection’s progression, with sustained high levels of Ghrelin counteracting inflammation. The TLR4/ MyD88/NF-κB pathway remained suppressed during the first 8 weeks, becoming activated only at 12 weeks. Inhibition of the MyD88 pathway resulted in reduced inflammation levels and upregulated Ghrelin expression, thereby collaboratively regulating the progression of hepatic infection.ConclusionThese findings suggest an interactive regulation between the MyD88 inflammatory signaling pathway and Ghrelin, indicating that MyD88 inhibition could enhance Ghrelin expression to modulate the progression of E. multilocularis infection.